2021
DOI: 10.1038/s41586-021-03946-w
|View full text |Cite
|
Sign up to set email alerts
|

Cascade of correlated electron states in the kagome superconductor CsV3Sb5

Abstract: The kagome lattice of transition metal atoms provides an exciting platform to study electronic correlations in the presence of geometric frustration and nontrivial band topology, which continues to bear surprises. In this work, using spectroscopic imaging scanning tunneling microscopy, we discover a cascade of different symmetry-broken electronic states as a function of temperature in a new kagome superconductor, CsV3Sb5. At a temperature far above the superconducting transition Tc ~ 2.5 K, we reveal a tri-dir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
283
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 407 publications
(320 citation statements)
references
References 55 publications
30
283
6
1
Order By: Relevance
“…The A 2 mode was also observed in another Raman study [53] and by time-resolved pump-probe spectroscopy [29,54]. However, in these works, it was suggested to emerge below ∼60 K [29,53,54], hence ascribed to another phase transition associated with the unidirectional 1 × 4 order [19,31,32]. According to our data, shown in Fig.…”
Section: Cdw-induced Modessupporting
confidence: 78%
See 3 more Smart Citations
“…The A 2 mode was also observed in another Raman study [53] and by time-resolved pump-probe spectroscopy [29,54]. However, in these works, it was suggested to emerge below ∼60 K [29,53,54], hence ascribed to another phase transition associated with the unidirectional 1 × 4 order [19,31,32]. According to our data, shown in Fig.…”
Section: Cdw-induced Modessupporting
confidence: 78%
“…The mechanism for the collapse of the crystal lattice in atomically thin CsV 3 Sb 5 could be related with the high chemical activity of the alkaline metal Cs. STM studies found nonuniform cleaved surfaces with clustered Cs atoms [31]. Refinement of X-ray diffraction data revealed high atomic displacement parameters for the Cs atoms, indicating their rattling-like motion owing to their weakly bonded nature [57].…”
Section: Thickness Dependencementioning
confidence: 99%
See 2 more Smart Citations
“…Here, the presence of linear bands, Dirac points, and band saddle points (van Hove singularities) in the electronic structure of a nearest-neighbor kagome metal causes multiple electronic instabilities that have been studied theoretically [1][2][3][4] but did not find their way into the lab until the recent discovery of the AV 3 Sb 5 compound family with A = K, Rb, Cs [5]. Both charge-density wave (CDW) order [6][7][8][9][10][11] and superconductivity [12][13][14][15][16][17] observed experimentally in these compounds closely resemble theoretical findings for a simple kagome metal with the Fermi energy lying near the van Hove singularity at the filling level of 5 12 [18,19]. In AV 3 Sb 5 , the corresponding saddle points are clearly visible in the vanadium bands around the M point slightly below the Fermi level (Fig.…”
Section: Introductionmentioning
confidence: 99%